Effect of open top chambers on soil microbiome and comparison between tropical and polar regions - Ng, Yi Ching (2020)
Soil contains the highest microbial diversity compared to other natural habitats on the earth. The advance in the next generation sequencing (NGS) techniques have allowed scientists to explore the diversity and composition of soil microorganisms at different locations including extreme cold places such as polar regions. Global warming has become an alarming issue to public as it could bring harms to all living organisms on earth. There are many studies reporting the effect of warming on the macroorganisms. However, not many studies reported on the response of microorganisms towards warming due to complexity of microbial genome. The importance of the study is to provide the reference knowledge for researchers on the relationship between the response of soil microbes and the effect of warming. The aim of this study was to compare soil metagenome between different months affected by open top chambers (OTC). A total of 18 soil samples were collected from 3 different open top chambers (OTC) located near the Molecular Biology Laboratory at Universiti Putra Malaysia between February and August 2017. The primer pairs 341F and 805R was employed to perform PCR amplifications of 16S rRNA gene and the samples were then sequenced on IlluminaMiseq2500 platform. The results showed that the most dominant bacterial phyla found within tropical soil samples were phyla Proteobacteria followed by Actinobacteria, Chloroflexi, Planctomycetes, Acidobacteria, Bacteroidetes, Firmicutes, Cyanobacteria, Verrucomicrobia, and Nitrospirae. After 6 months of OTC warming, the results showed that there was an increase in abundance of Proteobacteria, Actinobacteria, Firmicutes and Verrucomicrobia while Chloroflexi, Acidobacteria, Cyanobacteria, and Nitrospirae showed decrease in their abundance. No significant change in soil bacterial diversity and richness but there was a shift in bacterial structure and composition. On the other hand, to study the species diversity among samples compared to available database and compare the analysis of soil metagenome between tropical and polar regions, two soil samples from Greenwich Island, Antarctic and Hornsund, Spitsbergen, Arctic regions were utilized. These two samples were not simulated by OTC at these two polar regions. In addition, they were pre-collected and pre-sequenced separately from the current batch of tropical soil samples. The soil metagenome data between tropical and polar regions were then compared together to observe their differences in bacterial diversity and composition. The results showed that three most dominant phyla found within the tropical soil samples were phyla Proteobacteria, Actinobacteria, and Chloroflexi while for both polar regions, the most dominant groups were represented by phyla Proteobacteria, Actinobacteria, and TM7. Additionally, the results also showed that there was presence of some commonly shared bacterial groups which were dominated in both polar and tropical soils. To conclude, short-term OTC warming did not cause any changes in soil bacterial diversity and richness but did cause changes in bacterial abundance of certain bacterial groups and in turn shift the bacterial structure and composition. Additionally, two most abundant and dominant bacterial groups, Proteobacteria and Actinobacteria were revealed from tropical and polar regions when comparing their metagenome data.